Prognostic factors of epilepsy in patients with neonatal seizures history - Banani Sidiq; Elisabeth S. Herini; Tunjung Wibowo (Paediatrica Indonesiana, 2013)
Background Seizures in neonates are often associated withneurological disorders in early life, including epilepsy. Severalpossible prognostic factors may influence the development ofepilepsy in these patients.Objective To evaluate prognostic factors that may influence theoccurrence of epilepsy in the first two years of life in patients witha history of neonatal seizures.Methods We performed a cohort retrospective study on patientswith neonatal se izures in Sardjito Hospital during 2004-2009.Prognostic factors observed were gender, family history ofepilepsy, neonatal hypoglycemia, assisted labor, hypoxic ischemicencephalopathy, preterm infant delivery, and epileptic state.Results Hypoxic ischemic encephalopathy and epileptic stateincreased the risk of epilepsy (HR 5.8; 95%CI 1.63 to 20.43 andHR 6.3; 95%CI 2 .0 to 19. 70, respectively). Assisted labor, pretermdelivery, neonatal hypoglycemia, family history of epilepsy, andgender did not increase the risk of epilepsy in the first two yearsof life.Conclusion Hypoxic ischemic encephalopathy and epileptic statein neonates presenting with seizures are the prognostic factors tobe epileptic children during the first two years of life.